Effects and underlying processes of a mindfulness-based intervention with young elite figure skaters: Two case studies - Bernier, M.; Thienot, E.; Pelosse, E.; Fournier, J. F. (The Sport Psychologist, 2014)
This article examines the effects and underlying processes of a mindfulness-based intervention through two case studies. A one-season intervention designed according to the mindfulness approach was implemented with young elite figure skaters. Case studies were complemented with different measurement methods: a questionnaire assessing mindfulness skills, percent improvement on competition scores compared with a control group, and interviews with skaters and coaches during the intervention. The two case studies presented demonstrate how the young skaters developed their mindfulness skills and how these skills benefited their performance. They also show the limitations of this intervention type in young populations. Performance improvement and processes underlying the intervention are discussed in light of the results, and new perspectives are provided for adapting them to the particular needs of young athletes.